2022
DOI: 10.1155/2022/7398110
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Management of the Melting Process in a Latent Heat Triplex Tube Storage System Using Different Configurations of Frustum Tubes

Abstract: In this study, the energy charging mechanism is mathematically modeled to determine the impact of design modifications on the thermofluidic behavior of a phase change material (PCM) filled in a triplex tube containment geometry. The surface area of the middle tube, where the PCM is placed, is supported by single or multi-internal frustum tubes in vertical triplex tubes to increase the performance of the heating and cooling of the system. In addition to the ordinary straight triplex tubes, three more scenarios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Tiji et al [84] analyzed the energy charging process to investigate the influence of design alterations on the thermofluidic behavior of a PCM in a triplex tube. This was done to investigate how design changes affect a phase change material's thermofluidic behavior (PCM).…”
Section: Melting Enhancement Using Finsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tiji et al [84] analyzed the energy charging process to investigate the influence of design alterations on the thermofluidic behavior of a PCM in a triplex tube. This was done to investigate how design changes affect a phase change material's thermofluidic behavior (PCM).…”
Section: Melting Enhancement Using Finsmentioning
confidence: 99%
“…Materials that contain pores. Most investigations have demonstrated that increasing the heat transfer surface increases the amount of heat transfer between the phase change material and working fluid [68][69][70][71][72][73]. Because of its ease of production, cheap cost, and simplicity, using fins is the most effective method for increasing heat transfer in phase-change materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to create a novel phase change material for the storage of thermal energy, nano fluids were added to PCMs. The researchers discovered that by enhancing heat conductivity by adding Nano fluid to PCM, the melting process could be completed more quickly [22][23][24][25][26][27]. The authors claim that they are unaware of any prior research on the subject of evaluating the impact of an air bubble on the melting process of paraffin wax (PCMs) despite the fact that there have been several studies on the melting of PCMs in cylindrical cells.…”
Section: Introductionmentioning
confidence: 99%
“…21 Although PCMs have engaged the researcher's interest, they regularly suffer from low thermal conductivity and low thermal diffusion rates, prohibiting their widespread usage. 22 To solve this problem, scholars have been examining different techniques such as nanoparticle distribution within the heat transfer fluid (HTF), 23,24 channel modification, 25,26 the use of extended surfaces, 27,28 and composite PCMs 29,30 to improve thermophysical properties of the PCM. 31 For this issue, Khajuria et al 32 examined the effect of channel geometry on the heat transfer enhancement of a specific type of bio-PCM (honeybee wax) as a heat storage medium encompassed in the double pipe heat exchanger.…”
Section: Introductionmentioning
confidence: 99%